For quality education free from corruption and fraudulent actions - Lantero, Luca; Finocchietti, Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Quality education must by its very nature be free of all forms of corruption and fraudulent actions, and more generally inspired by the principles of ethics, transparency and integrity. If the statement may seem obvious, it is less trivial to translate it into practice, especially in the context of complex national systems and transnational actions between educational institutions, which are increasingly common in the academic sphere. National systems, international organisations (Council of Europe, European Commission, UNESCO) and international reference processes, such as the European Higher Education Area, are adopting policies for the development of education systems inspired by principles based on ethics, transparency and integrity.